Akulturasi Islam dalam Perkawinan Adat Dayak Ngaju: Sejarah Masyarakat Muslim di Desa Petak Bahandang, Kabupaten Katingan, Kalimantan Tengah - Nor Ani; Abubakar Abubakar; Muhammad Iqbal (LP2M IAIN Palangka Raya, 2019)
Islamic acculturation in traditional Ngaju Dayak marriage: History of Muslim communities in Petak Bahandang Village, Katingan Regency, Central Kalimantan. There are three main issues to be discussed in this paper, namely how is the history of the village, how is the history and procession of traditional marriages and how is the acculturation of Islamic values and local culture in traditional marriages carried out by the Dayak Ngaju ethnic Muslim community. This article uses a type of historiographic research using a spoken history approach. The findings concluded that the Muslim community of Dayak Ngaju in Katingan Regency, Central Kalimantan Province, is still carrying out customary marriages. For them, the purpose of carrying out a traditional marriage is not as a symbol of the validity of a marriage relationship, but to preserve local wisdom and is a prevention of divorce by making an agreement. Muslim communities still have to fulfill the path of hadat drawn from the maternal lineage and in the procession the Muslim community first conducts a marriage according to religion. After that, they conduct a marriage according to the custom. This custom marriage represents Islamic values.